2014
DOI: 10.4103/1658-354x.136637
|View full text |Cite
|
Sign up to set email alerts
|

Fiberoptic intubation through laryngeal mask airway for management of difficult airway in a child with Klippel-Feil syndrome

Abstract: The ideal airway management modality in pediatric patients with syndromes like Klippel-Feil syndrome is a great challenge and is technically difficult for an anesthesiologist. Half of the patients present with the classic triad of short neck, low hairline, and fusion of cervical vertebra. Numerous associated anomalies like scoliosis or kyphosis, cleft palate, respiratory problems, deafness, genitourinary abnormalities, Sprengel's deformity (wherein the scapulae ride high on the back), synkinesia, cervical ribs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…5,6 Flexible bronchoscopic intubation through a slit Guedel tube remains one of the most common practices in expected difficult intubation, yet bronchoscopic intubation via a supraglottic airway may now be considered an alternative approach. 2,[7][8][9][10] This is an easier alternative for the management of the difficult airway, as it offers younger less experienced anesthesia providers an easier handling method to gain sufficient and safe practice in bronchoscopic awake intubation. 11 Orotracheal bronchoscopic intubation may be facilitated by diverse airway or supraglottic devices, such as the slit Guedel tube or the Ovassapian airway (Hudson RCIÒ), which help guide the flexible bronchoscope to the glottic opening.…”
mentioning
confidence: 99%
“…5,6 Flexible bronchoscopic intubation through a slit Guedel tube remains one of the most common practices in expected difficult intubation, yet bronchoscopic intubation via a supraglottic airway may now be considered an alternative approach. 2,[7][8][9][10] This is an easier alternative for the management of the difficult airway, as it offers younger less experienced anesthesia providers an easier handling method to gain sufficient and safe practice in bronchoscopic awake intubation. 11 Orotracheal bronchoscopic intubation may be facilitated by diverse airway or supraglottic devices, such as the slit Guedel tube or the Ovassapian airway (Hudson RCIÒ), which help guide the flexible bronchoscope to the glottic opening.…”
mentioning
confidence: 99%
“…5,9 Furthermore, it has been documented as being utilized in combination with fiberoptic bronchoscopy as a primary step in endotracheal intubation in patients with difficult visualization. 13,14 Chen and Hsiao demonstrated 90.5% correct position placement by paramedic students in a normal airway during a simulated pediatric resuscitation scenario. 5 A study by Guyette et al demonstrated a 100% LMA insertion rate in testing paramedic students in a similar normal scenario.…”
Section: Discussionmentioning
confidence: 99%
“…It is a defined treatment in difficult and craniofacial pediatric airways and, once learned, becomes an expeditious way to secure an advanced airway without the need for direct visualization 5,9 . Furthermore, it has been documented as being utilized in combination with fiberoptic bronchoscopy as a primary step in endotracheal intubation in patients with difficult visualization 13,14 . Chen and Hsiao demonstrated 90.5% correct position placement by paramedic students in a normal airway during a simulated pediatric resuscitation scenario 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the Laryngeal Mask Airway Classic and Unique have been used successfully as conduits for fiberoptic intubation in children, their airway tube design makes them less than ideal. Having a long, narrow airway tube creates many obstacles, especially when trying to remove the SGA when a cuffed tracheal tube is used.…”
Section: Characteristics Of the Perfect Pediatric Sgamentioning
confidence: 99%